El desarrollo del pensamiento crítico y su influencia en la relación del docente con el estudiante en el aula - Núñez Córdova, Juan Emanuel (2015)
This article conceives the critical thinking as a fundamental tool for human learning, it helps to clarify ideas and provides a solution to the problems in the pedagogical relationship and in the learning process. This research paper examines the main skills of critical thinking and interpretation, inference, analysis, self-regulation, explanation and evaluation, aiming to become an introductory material for the improvement of educational work; as students entering secondary education have serious difficulties in the management of basic thinking skills to aspire to academic and existential success. Also, it concludes by proposing an example for the implementation of one of the critical thinking skills such as the resolution of problems.